(untitled) (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Jabar L, Siebert SJ, Pfab MF, Cilliers DP. 2021. Population biology and ecology of the endangered Euphorbia susannae Marloth, an endemic to the Little Karoo, South Africa. Biodiversitas 22: 4583-4596. Many euphorbias in the semi-arid parts of South Africa are restricted edaphic specialists with small populations at risk of extinction. Euphorbia susannae is one such species, which grows on the edges of quartz patches along a section of the northern foot slopes of the Langeberg Mountains. This study set out to acquire data on the biology and ecology of the species during a first-ever comprehensive field survey. The resultant dataset allowed for the determination of the geographic distribution of the species, as well as the size and number of populations. Biotic and abiotic environmental variables were employed to generate a habitat profile and a species distribution model. The population structure, regeneration potential, and stability of each subpopulation and the population were also assessed. Euphorbia susannae is a range-restricted species (EOO 170 km2 and AOO 36 km2) confined to eight subpopulations that vary considerably in size. According to this study, 1845 individuals remain in the wild. Habitat preferences of the species were considered in detail and linked to a species distribution model for conservation purposes. It was shown that the species preferred nurse plants. The smallest adults size class was the largest cohort in all the sub-populations and was ascribed to pulse recruitments after an unknown favorable event. Although individuals were not evenly distributed among the size classes, annual recruitments levels were healthy, suggesting good pollination, seed set, and germination conditions.